Disturbing the balance: effect of contact lens use on the ocular proteome and microbiome. (3rd August 2017) - Boost, Maureen; Cho, Pauline; Wang, Zhaoran
Abstract : Contact lens wear is a popular, convenient and effective method for vision correction. In recent years, contact lens practice has expanded to include new paradigms, including orthokeratology; however, their use is not entirely without risk, as the incidence of infection has consistently been reported to be higher in contact lens wearers. The explanations for this increased susceptibility have largely focused on physical damage, especially to the cornea, due to a combination of hypoxia, mechanical trauma, deposits and solution cytotoxicity, as well as poor compliance with care routines leading to introduction of pathogens into the ocular environment. However, in recent years, with the increasing availability and reduced cost of molecular techniques, the ocular environment has received greater attention with in‐depth studies of proteins and other components. Numerous proteins were found to be present in the tears and their functions and interactions indicate that the tears are far more complex than formerly presumed. In addition, the concept of a sterile or limited microbial population on the ocular surface has been challenged by analysis of the microbiome. Ocular microbiome was not considered as one of the key sites for the Human Microbiome Project, as it was thought to be limited compared to other body sites. This was proven to be fallacious, as a wide variety of micro‐organisms were identified in the analyses of human tears. Thus, the ocular environment is now recognised to be more complicated and interference with this ecological balance may lead to adverse effects. The use of contact lenses clearly changes the situation at the ocular surface, which may result in consequences which disturb the balance in the healthy eye.